Sistem Manajemen Seni Pertunjukan Sanggar Seni Sabai Nan Aluih Di Kurao Pagang Kota Padang - Ledy Sintia; Afifah Asriati (FBS Universitas Negeri Padang, 2022)
This research aims to explain and describe the Art Galeri Sabai Nan Aluih Performing Arts Management System in Kurao Pagang Kota Padang. This type of research is qualitative research using descriptive methods. The instruments in this study were researchers themselves using supporting instruments such as stationery and cameras. The types of data used are primary data and secondary data. The data collection techniques used in this study are literature studies, observations, interviews and documentation. The data analysis techniques used in this study use data reduction activities, presentation of data and concluding/verification. The results of this study show that Sanggar Seni Sabai Nan Aluih has a single leadership management system. Its implementation is assisted by the sovereignty of the core dancers. Art Galeri Sabai Nan Aluih's performance arts management system rests on project management, marketing management and financial management. The project management of Art Galeri Sabai Nan Aluih adjusts to the demand for performances from consumers, in addition to Art Galeri also having dance provisions displayed at each event. To produce dance works includes factors of production such as material materials, capital, labour, equipment and information.